Early evolution of bHLH proteins in plants. - Pires, N; Dolan, L (2010)
Basic-helix-loop-helix (bHLH) proteins are a large family of eukaryotic transcription factors. In plants, they have been shown to be key regulators of a diverse array of developmental and metabolic pathways. We have recently shown that the diversity of bHLH proteins in angiosperms is ancient. Most of the bHLH subfamilies present in seed plants such as Arabidopsis thaliana and Oryza sativa are also present in early diverging groups of land plants, including mosses and lycophytes. In contrast, the diversity of bHLH proteins is much lower in chlorophytes (green algae) and red algae. This suggests that the bHLH family underwent a large expansion before or soon after the appearance of the first land plants, but has subsequently remained relatively conserved throughout the evolution of plants on land. These observations support the developing paradigm that land plants (and other complex multicellular organisms) have evolved largely through the recruitment and reorganization of ancient gene regulatory networks.